Analisis Persentase Indeks Kadar CPO (Crude Palm Oil) di PTPN III Aek Nabara Kecamatan Bilah Hulu - Zulfikar Ritonga (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
Percentage Analysis of CPO (Crude Palm Oil) Index In PKS PTPN III Aek Nabara SelatanKecamatan Bilah upstream. Under the guidance of Ms. Yusmaidar Sepriani, S.Pd, M. Si, and Mr.Dede Suhendra, SP, MP.The results of this study by presenting the data using IBM SPSS 20.0 canbe concluded the results of multiple linear regression calculation declared the amount of CPOproduction (Crude Palm Oil) to the influence of Free Fatty Acids, Water Content, Impurity Contentin PKS PTPN III Aek Nabara Selatan Kecamatan Bilah Hulu. This shows the results of a strongand positive drajat get value of 0.8 close to 1 it means to have the effect of the amount of CPOproduction (Crude Palm Oil) in PKS PTPN III Kebun Aek Nabara Selatan with the value of RSquare sebeasar 0.008 can be interpreted that the influence of Fatty Acids Free, Water Content,Impurities Concentration to the production amount of 8 percent (0.8) while the remaining 98.2percent is influenced by other models not included in the tes.